Leverage and Liquidity Ratio on Islamic Social Reporting Disclosures on Property Companies - Ely Windarti Hastuti; Farah Salsabila; Salysya Dzakiyah Al Abidah (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
It is important to know the performance of a company to evaluate the level of company activity in a certain period. Measurement of company performance can be seen from financial and non-financial performance. Some of the ratios used to measure the company's financial performance include liquidity and leverage ratios. Meanwhile, the performance of non-financial companies can be seen from the disclosure of social responsibility. The standard for disclosure of social responsibility that takes into account the aspects of Islamic is Islamic social reporting. In addition, companies must also pay attention to the aspects of accountability and transparency in calculating financial performance and disclosure of social responsibility. The purpose of this research is to analyze the effect of liquidity ratios and leverage in social responsibility disclosure in property sector companies. This type of research is quantitative. The sample used is 21 major sector property companies in Indonesia in the 2015-2019 period. The data analysis technique used is multiple linear regression analysis and Moderated Regression Analysis (MRA) because this research uses two independent variables and a moderating variable. The results showed that the leverage and liquidity variables partially has a positive and not significant effect on social responsibility disclosure.